(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Rickets remains a significant metabolic bone disorder in children, primarily resulting from vitamin D deficiency and impaired mineralization of growing bones. Vitamin D plays a central role in calcium and phosphorus homeostasis, intestinal absorption of minerals, and normal skeletal development. This article provides a comprehensive overview of the importance of vitamin D in the treatment of rickets, with particular emphasis on its absorption, metabolic activation, and therapeutic effectiveness. The paper analyzes clinical and biochemical outcomes associated with vitamin D supplementation and highlights its role in restoring bone structure, preventing deformities, and improving overall growth parameters in affected children. Understanding the mechanisms underlying vitamin D action is essential for optimizing treatment strategies and preventing long-term complications of rickets. This work examines the therapeutic importance of vitamin D in the management of rickets, focusing on its physiological influence on mineral balance and skeletal recovery. Emphasis is placed on how adequate supplementation improves intestinal uptake of essential elements, supports proper bone formation, and accelerates clinical improvement in affected children. The analysis highlights the clinical relevance of timely intervention and demonstrates that appropriate correction of deficiency leads to measurable biochemical normalization and structural bone repair, reducing the risk of long-term deformities and functional limitations.